The Abdominal-B gene of Drosophila melanogaster: overlapping transcripts exhibit two different spatial distributions - Sánchez-Herrero, Ernesto (1988)
The Abdominal-B (Abd-B) gene of Drosophila controls the specification of segment identities in the posterior abdomen. We describe here the spatial and temporal distribution of Abd-B transcripts. At least five RNA species are detected on Northern blots with probes within the region of the Abd-B homeobox. We have identified probes specific for subsets of these transcripts and have used these probes to study the distribution of each subset by in situ hybridization to embryonic tissue sections. The transcripts can be divided into two groups: one group is expressed maximally in parasegment (PS)13 and extends anteriorly to PS10; the other is expressed only in PS14 and 15. These two different patterns of expression correspond to the anatomical domains defined by two classes of mutations in Abd-B. These results help explain the complex genetic interactions and phenotypes of mutations within this gene.